Evaluasi Kurikulum Pendidikan Agama Islam Perspektif Multikultural di Sekolah Menengah Pertama - Mainah, Mainah; Wahyuni, Sri (Kartika: Jurnal Studi Keislaman, 2025)
The Islamic Religious Education Curriculum (PAI) plays a crucial role in shaping students’ character and tolerance attitudes within the context of cultural and religious diversity. This study aims to evaluate the PAI curriculum at SMPN 11 Sungai Ambawang by analyzing the Core Competencies (KI) and Basic Competencies (KD) from a multicultural perspective. The research employed a qualitative approach with document analysis of KI and KD, complemented by teacher interviews and classroom observations. The findings reveal that KI and KD incorporate multicultural values such as tolerance and respect for differences; however, these remain conceptual and require reinforcement through clearer and more practical competency achievement indicators. The main challenges in curriculum implementation include limited teacher capacity and a lack of multicultural-supporting learning resources. The study recommends revising KI and KD to explicitly integrate multicultural principles and enhancing teacher training and development of contextual, inclusive learning materials. The implications of this study are significant for developing a PAI curriculum responsive to social diversity in Indonesia.